1986
DOI: 10.1001/archinte.146.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' assessment of cognitive capacity. Failure to meet the needs of the elderly

Abstract: The major task of medicine with the geriatric population is to assist with the promotion of a vigorous quality of life and maintenance of function. The key to functioning is cognitive capacity. Evidence is offered that physicians are still not assessing their patients' intellectual functioning, despite its importance not just for coping, but also for the very maintenance of life. Dementia and delirium are too frequently missed. Deficits in attitude, skill, and knowledge all contribute to this failure. It must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Failure to recognize delirium or misdiagnosis of delirium is common [13,50,59,68,69,77]. Bruera et al reported that in patients admitted to a palliative care unit, routine conversation without an objective assessment of cognition resulted in the diagnosis of cognitive impairment being missed by physicians and nurses in 23% and 20% of cases, respectively [13].…”
Section: Issues In the Recognition Of Deliriummentioning
confidence: 99%
“…Failure to recognize delirium or misdiagnosis of delirium is common [13,50,59,68,69,77]. Bruera et al reported that in patients admitted to a palliative care unit, routine conversation without an objective assessment of cognition resulted in the diagnosis of cognitive impairment being missed by physicians and nurses in 23% and 20% of cases, respectively [13].…”
Section: Issues In the Recognition Of Deliriummentioning
confidence: 99%
“…Moreover, physicians fail to recognize a high proportion of patients with cognitive defects under their care (McCartney, 1986). There is no reason to believe that surgeons are any more competent in this respect.…”
Section: Diagnosismentioning
confidence: 99%
“…"False negatives" in which the presence of dementia is missed, remain common, primarily due to failure to appreciate dementia in the setting of psychiatric illness. 98 Up to 80% of the normal elderly will note some deterioration in memory over time and sometimes complain of this. 99 Patients with depression but no dementia may complain of subjective memory loss quite strongly, although no objective evidence of memory difficulties is found on formal testing.…”
Section: Historymentioning
confidence: 99%
“…98 The MSE is time consuming and in practice often relies on a limited battery of memory and cognitive tests or else screening tools such as the MMSE. 112 Even simple screening tests can be highly useful in that they can support the objective presence of memory impairment.…”
Section: Mental Status Testing and Neuropsychological Screeningmentioning
confidence: 99%